The Role of the Management of the Al-Rahmah Walantaka Islamic Boarding School in Facilitating the Mental Well-being of Students Through the Management Discipline Policy - Siti Elya Fitrianingsih; Enung Nurhayati; Faturrahman Faturrahman; Aaf Afiah Aaf Afiah; Encep Syarifudin; Deni Iriyadi (Journal of Educational Sciences, 2026)
The pesantren environment functions as a comprehensive educational institution whose management significantly influences students’ mental well-being. This study examines the role of management at Al Rahmah Islamic Boarding School in supporting students’ mental health, particularly through disciplinary policies and administrators’ communication capacity. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and policy document analysis, then analyzed thematically. The findings indicate that disciplinary policies are designed as part of character building rather than purely repressive measures. However, discrepancies between policy ideals and practical implementation may create psychological pressure for students. Administrators’ communication skills, especially interpersonal and transcultural communication, are crucial in translating disciplinary norms into constructive understanding. Effective communication fosters motivation, reduces conflict, and supports students’ mental well-being. The study concludes that pesantren management plays a strategic role in facilitating mental well-being, emphasizing that supportive communication and dialogical relationships are more influential than strict rules alone. Continuous communication training and regular evaluation of disciplinary policies based on rahmatan lil ‘alamin principles are recommended.